Barriers to self-care and their association with poor adherence to self-care behaviours in people with type 2 diabetes in Ghana: A cross sectional study. (June 2020) - Mogre, Victor; Johnson, Natalie A.; Tzelepis, Flora; Hall, Alix; Paul, Christine
Abstract: Aim: We evaluated the prevalence of barriers to self-care and associations between these barriers and adherence to self-care behaviours among people with type 2 diabetes. Methods: Cross-sectional study among people with type 2 diabetes recruited from the diabetes clinics of three hospitals. A survey assessed barriers to self-care conceptualised into the constructs of the theory of planned behaviour (TPB) (i.e. attitudes, subjective norms, perceived behavioural control). The Summary of Diabetes Self-care Activities scale was used to assess adherence to self-care. Results: The study included 252 (90% response rate) participants. Prevalent barriers included: lack of knowledge on how to use a glucometer (59.8%, n = 150); difficulty in changing dietary habits (58.7%, n = 148); and lack of money to purchase a glucometer (55.2%, n = 139). Attitudinal barriers were commonly reported for diet, exercise and foot care; perceived behavioural control barriers were frequently reported for self-monitoring of blood glucose (SMBG); and subjective norm barriers for medication taking. The only significant association was between adherence to foot care and subjective norms barriers. Conclusions: The commonly-reported types of barriers varied according to the type of self-care behaviour but no specific type of barrier was associated with poor adherence to diabetes self-care behaviours. Highlights: Barriers to diabetes self-care are frequently reported by people with type 2 diabetes. Barriers to diet, exercise and foot care are generally attitudinal. Barriers may not be associated with poor adherence to diabetes self-care.